A third wave of autocratization is here: what is new about it?. Issue 7 (3rd October 2019) - Lührmann, Anna; Lindberg, Staffan I.
ABSTRACT: Less than 30 years after Fukuyama and others declared liberal democracy's eternal dominance, a third wave of autocratization is manifest. Gradual declines of democratic regime attributes characterize contemporary autocratization. Yet, we lack the appropriate conceptual and empirical tools to diagnose and compare such elusive processes. Addressing that gap, this article provides the first comprehensive empirical overview of all autocratization episodes from 1900 to today based on data from the Varieties of Democracy Project (V-Dem). We demonstrate that a third wave of autocratization is indeed unfolding. It mainly affects democracies with gradual setbacks under a legal façade. While this is a cause for concern, the historical perspective presented in this article shows that panic is not warranted: the current declines are relatively mild and the global share of democratic countries remains close to its all-time high. As it was premature to announce the "end of history" in 1992, it is premature to proclaim the "end of democracy" now.